Determination of the Parameters of a Phase Change Material That Can be Used in The Condenser Sector of Domestic Freezers (Damascus University Journal for engineering sciences, 2024)
Thermal energy storage (TES) is nowadays one of the most feasible solutions in facing the challenge of achieving energy savings. Many researchers have investigated energy efficiency of different cold units by applying TES systems using phase change materials (PCMs). In this paper, the type and thickness of the phase change material that can be used in domestic freezers was determined to increase the coefficient of performance and reduce energy consumption at room temperature condition of 32 °C. At steady state the compressor runs for 15 min and stops working for 10 min. computational simulations of two different paraffins were performed. Eicosane paraffin with a thickness of 9 mm was considered to be the best in terms of thermal performance under the imposed problem conditions.
Keywords: Domestic Freezer; Phase Change Materials (PCMs); Paraffin Wax; Solid-Liquid Phase Transition, Melting Temperature; Phase Change Material Thickness